Treatment of chronic heart failure with pirbuterol: acute haemodynamic responses. Issue 6274 (2nd May 1981) - Dawson, J R; Canepa-Anson, R; Kuan, P; Whitaker, N H; Carnie, J; Warnes, C; Reuben, S R; Poole-Wilson, P A; Sutton, G C
Abstract : Fifty-nine patients with severe chronic heart failure were given pirbuterol, a beta agonist with vasodilator and positive inotropic properties. The acute haemodynamic responses to both single (20 patients) and incremental doses (39 patients) were measured. Pirbuterol increased cardiac index and reduced left ventricular filling pressure and systemic vascular resistance with only small changes in heart rate and blood pressure. Maximal effects were observed at an average of 170 minutes after a single oral dose of pirbuterol. In the incremental dose studies the plasma pirbuterol concentration was found to increase with increasing doses and was related to the magnitude of the haemodynamic response. Pirbuterol was well tolerated, and no drug-related side effects were recorded. Oral pirbuterol clearly improved pump performance in these patients, the haemodynamic changes being consistent with vasodilatation as the dominant mechanism rather than a direct inotropic effect.